Austenitic ferritic duplex stainless steel sheet for fuel cell separator

By optimizing the composition of the stainless steel plate, the austenitic ferrite duplex stainless steel plate is made, which solves the problem of corrosion of the stainless steel plate in the fuel cell environment, achieves high corrosion resistance and excellent stamping processing, and extends the life of the fuel cell stack.

CN119908040APending Publication Date: 2025-04-29JFE STEEL CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380060754.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-22
Filing Date
2023-06-06
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The stainless steel plate for existing fuel cell separators is easily corroded when in contact with the water generated by the fuel cell, resulting in Fe ions dissolution, reducing the proton conductivity and power generation characteristics of the electrolyte membrane, and affecting the longevity of the fuel cell.

Method used

By optimizing the composition of the stainless steel plate, the Cr content and N content are increased, and the Ni content is reduced, the austenitic ferrite duplex stainless steel plate is made, which enhances its Fe ion dissolution resistance while maintaining excellent stamping processability.

Benefits of technology

It realizes high corrosion resistance of stainless steel plates in fuel cell environments, reduces Fe ion dissolution, extends the life of fuel cell stacks, and takes into account stamping processability. It is suitable for high-demand applications such as commercial vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119908040A_ABST
    Figure CN119908040A_ABST
Patent Text Reader

Abstract

Provided is a stainless steel sheet for fuel cell separators, which has both excellent press workability and Fe ion elution resistance. The steel sheet has a component composition having, in mass%, 18.0-24.0% of Cr and 3.00% or less of Ni, the steel structure containing an austenite phase and a ferrite phase, the fraction of the austenite phase being 30% or more, the total fraction of the austenite phase and the ferrite phase being 95% or more, and the total elongation being 40% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an austenite-ferrite duplex stainless steel plate for a fuel cell separator. Background Art

[0002] Fuel cells are classified into phosphoric acid fuel cells, molten carbonate fuel cells, solid oxide fuel cells, alkali fuel cells, and solid polymer fuel cells (proton-exchange membrane fuel cell or polymer electrolyte fuel cell, hereinafter also referred to as PEFC) according to the type of electrolyte membrane used.

[0003] Among these fuel cells, PEFC has a relatively low operating temperature of 100°C or less, and is easy to start and stop. Therefore, research has been ongoing on the use of PEFC in automotive power sources, household or commercial stationary generators, and portable small generators. In particular, fuel cell vehicles (FCVs) equipped with fuel cells as power sources are expected to be the application targets of PEFC.

[0004] Generally, a fuel cell is composed of an electrolyte membrane, an electrode, a gas diffusion layer, and a bipolar plate. PEFC separators are mostly made of graphite. Graphite separators have the advantages of low contact resistance and no corrosion. On the other hand, graphite separators have the disadvantages of being easily damaged by impact, high processing costs, and difficulty in thinning.

[0005] Therefore, the application of metal separators using stainless steel or titanium alloy as substrate materials has been studied. Metal separators are superior in processability and strength compared to graphite separators. Therefore, by adopting metal separators, it is expected that the fuel cell can be miniaturized and the processing cost of the separator can be reduced.

[0006] Generally, the separator is required to have a low electrical resistance (hereinafter also referred to as contact resistance) with the gas diffusion layer and other separators. In addition, the separator is subjected to a stamping process for forming a groove as a flow path for gas or cooling water. Therefore, as a substrate material used in a metal separator, stainless steel subjected to a surface treatment for ensuring contact resistance, in particular, austenitic stainless steels such as SUS304 and SUS316L having excellent stamping processability, have been studied and applied.

[0007] For example, Patent Documents 1 and 2 disclose a fuel cell separator using, as a substrate material, austenitic stainless steel of SUS304 or SUS316L having a coating such as gold plating or a carbon thin film on the surface.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent No. 3854682

[0011] Patent Document 2: Japanese Patent No. 4147925 Summary of the invention

[0012] However, in recent years, the electrification of automobiles has developed rapidly. However, electric vehicles (BEVs) equipped with rechargeable secondary batteries are not suitable for long-distance transportation purposes. Therefore, it is believed that the main application objects of FCVs are trucks for long-distance transportation, commercial vehicles such as buses and taxis with fixed routes and easy infrastructure development.

[0013] Commercial vehicles require better durability and reliability than passenger vehicles. Therefore, the fuel cell stack mounted on commercial vehicles needs a longer life. In particular, if the stainless steel used in the separator is corroded by contact with water generated by the power generation reaction of the fuel cell (hereinafter also referred to as PEFC generated water) and Fe ions are dissolved, the proton conductivity of the electrolyte membrane (polymer membrane) is reduced and the power generation characteristics are reduced. Therefore, the long life of the fuel cell stack requires a high level of suppression of the dissolution of Fe ions from the stainless steel used in the separator.

[0014] Regarding this point, the fuel cell separator disclosed in patent documents 1 and 2 utilizes the coating on the surface of the substrate material to suppress the dissolution of Fe ions from stainless steel to a certain extent. However, if the coating produces defects, Fe ions will dissolve through the defects. In particular, if stamping is performed after forming a coating on the surface of stainless steel, defects are easily generated in the coating, and the dissolution of Fe ions through the defects will become a serious problem. In addition, from the perspectives of productivity and miniaturization of fuel cells, it is not desirable to form a coating or make the coating too thick after stamping stainless steel. Therefore, it is urgent to improve the Fe ion dissolution resistance of the fuel cell separator stainless steel plate itself (stainless steel plate in a state where a coating is not formed) used in the substrate material.

[0015] The present invention has been developed in view of the above-mentioned current situation, and an object of the present invention is to provide a stainless steel plate for a fuel cell separator having both excellent press workability and resistance to Fe ion elution.

[0016] The present inventors have conducted intensive studies to solve the above-mentioned problems and have obtained the following findings.

[0017] As the Cr content increases, the Fe ion dissolution resistance increases. That is, if the Cr content increases, the stability of the passive film formed on the surface of the stainless steel plate increases. This can suppress the corrosion (dissolution) of the stainless steel caused by contact with an acidic aqueous solution such as PEFC generated water.

[0018] However, if the Cr content is too high, the punchability decreases.

[0019] Therefore, the present inventors have studied whether there are other means for improving the resistance to Fe ion dissolution besides increasing the Cr content, and have obtained the following findings.

[0020] If the Cr content is the same, the lower the Ni content, the higher the resistance to Fe ion dissolution.

[0021] When the Ni content decreases, the fraction of the austenite phase decreases, and sufficient stamping workability cannot be obtained.

[0022] By containing an appropriate amount of N, the fraction of the austenite phase can be ensured even if the Ni content is small. This makes it possible to achieve both excellent stamping workability and resistance to Fe ion dissolution.

[0023] Furthermore, the present inventors have conducted further studies based on the above findings and have obtained the finding that a stainless steel sheet having both excellent press workability and resistance to Fe ion dissolution can be obtained by satisfying the following component composition and steel structure simultaneously.

[0024] The component composition includes, by mass%, 18.0 to 24.0% Cr, 3.00% or less Ni, and 0.100 to 0.300% N.

[0025] Austenite-ferrite duplex stainless steel sheet is produced. Specifically, the fraction of the austenite phase is set to 30% or more, and the total fraction of the austenite phase and the ferrite phase is set to 95% or more.

[0026] It should be noted that, hereinafter, the austenite phase is also referred to as the γ phase, and the ferrite phase is also referred to as the α phase. In addition, the fraction of the austenite phase is also referred to as the γ phase fraction, the fraction of the ferrite phase is also referred to as the α phase fraction, and the total fraction of the austenite phase and the ferrite phase is also referred to as the γ phase + α phase fraction.

[0027] The present invention has been completed as a result of further studies based on the above findings.

[0028] That is, the gist of the present invention is as follows.

[0029] 1. An austenitic ferritic duplex stainless steel plate for a fuel cell separator, the composition of which is Cr: 18.0-24.0%, Ni: 3.00% or less, and N: 0.100-0.300%, in terms of mass %.

[0030] The steel structure has austenite phase and ferrite phase.

[0031] The austenite phase fraction is 30% or more.

[0032] The total fraction of the austenite phase and the ferrite phase is 95% or more,

[0033] The total elongation is more than 40%.

[0034] 2. The austenitic-ferritic duplex stainless steel sheet for a fuel cell separator according to item 1 above, wherein the sheet thickness is 0.03 to 0.30 mm.

[0035] 3. The austenitic-ferritic duplex stainless steel sheet for a fuel cell separator according to 1 or 2 above, which has a coating layer of a conductive material on the surface.

[0036] According to the present invention, a stainless steel plate for a fuel cell separator having both excellent press workability and resistance to Fe ion elution can be obtained.

[0037] Furthermore, by using the stainless steel plate for a fuel cell separator of the present invention, a fuel cell stack having excellent durability and reliability can be manufactured, and further a fuel cell vehicle (FCV) can be manufactured. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a schematic diagram of a test piece used for evaluating the resistance to Fe ion elution. DETAILED DESCRIPTION

[0039] [1] Ingredients

[0040] First, the composition of the austenitic ferritic duplex stainless steel plate for a fuel cell separator according to one embodiment of the present invention (hereinafter also referred to as the stainless steel plate according to one embodiment of the present invention) is described. It should be noted that the units in the composition are all "mass %", and hereinafter, unless otherwise specified, only "%" is used.

[0041] Cr: 18.0~24.0%

[0042] Cr is an element that stabilizes the passive film of stainless steel and reduces the solubility of Fe ions. When the Cr content is less than 18.0%, sufficient resistance to Fe ion dissolution cannot be obtained. On the other hand, Cr is an α-phase generating element. Therefore, if the Cr content exceeds 24.0%, it is difficult to obtain a sufficient amount of γ-phase fraction. Therefore, the Cr content is set to 18.0-24.0%. The Cr content is preferably 19.0% or more, and more preferably 20.5% or more. In addition, the Cr content is preferably 23.0% or less, and more preferably 22.0% or less.

[0043] Ni: 3.00% or less

[0044] Ni is an element that reduces the resistance to Fe ion dissolution. In particular, if the Ni content exceeds 3.00%, the adverse effect on the resistance to Fe ion dissolution becomes significant. Therefore, the Ni content is set to 3.00% or less. The Ni content is preferably 2.50% or less, more preferably 2.00% or less, and further preferably 1.00% or less. On the other hand, Ni is an element that stabilizes the γ phase. In order to obtain this effect, the Ni content is preferably 0.10% or more.

[0045] N: 0.100~0.300%

[0046] N is a γ phase generating element. That is, N has the effect of stabilizing the γ phase instead of Ni and increasing the γ phase fraction. In addition, N is also an element that improves the corrosion resistance of stainless steel. In order to obtain these effects, N is contained at 0.100% or more. On the other hand, if the N content exceeds 0.300%, pores may be generated during casting. In addition, pressure treatment is required for dissolving N contained in steel, resulting in an increase in manufacturing costs. Therefore, the N content is set to 0.100-0.300%. The N content is preferably 0.150% or more. In addition, the N content is preferably 0.250% or less, and more preferably 0.200% or less.

[0047] The elements other than the above are not particularly limited as long as the steel structure described below can be obtained. For example, as a preferred component composition of a stainless steel plate according to one embodiment of the present invention, the following component composition can be exemplified:

[0048] C: 0.200% or less, Si: 1.00% or less, Mn: 7.00% or less, P: 0.100% or less, S: 0.030% or less, Cr: 18.0-24.0%, Ni: 3.00% or less, Al: 0.100% or less, Cu: 4.00% or less, Mo: 4.00% or less, and N: 0.100-0.300%,

[0049] It optionally further contains one or more selected from Ti: less than 0.50%, Nb: less than 0.50%, V: less than 0.50%, Zr: less than 0.50%, Sn: less than 0.50%, B: less than 0.0100%, Ca: less than 0.0100%, Mg: less than 0.0100% and REM: less than 0.10%, and the remainder is Fe and unavoidable impurities.

[0050] The preferred component composition is described below. It should be noted that Cr, Ni and N are as described above, and their description is omitted here.

[0051] C: 0.200% or less

[0052] C is an element that stabilizes the γ phase. In order to obtain this effect, it is preferred to contain 0.003% or more of C. On the other hand, if the C content exceeds 0.200%, the heat treatment temperature for dissolving C becomes high, and productivity may decrease. Therefore, the C content is preferably 0.200% or less. The C content is more preferably less than 0.050%, further preferably less than 0.030%, and further preferably less than 0.020%.

[0053] Si: 1.00% or less

[0054] Si is an element that acts as a deoxidizer. In order to obtain this effect, it is preferred to contain 0.01% or more Si. On the other hand, if the Si content exceeds 1.00%, the strength becomes too high and the cold workability decreases. In addition, Si is an α-phase generating element. Therefore, if the Si content exceeds 1.00%, it is sometimes difficult to obtain the desired γ phase fraction. Therefore, the Si content is preferably 1.00% or less. The Si content is more preferably 0.70% or less, further preferably 0.50% or less, and further preferably 0.35% or less.

[0055] Mn: 7.00% or less

[0056] Mn is an element that stabilizes the γ phase. In addition, Mn has the effect of increasing the solid solution amount of N in the α phase and preventing the sensitization of the α phase grain boundary. In order to obtain these effects, it is preferred to contain 0.01% or more of Mn. The Mn content is more preferably 1.00% or more, and further preferably 2.00% or more. On the other hand, if the Mn content exceeds 7.00%, hot workability and corrosion resistance may decrease. Therefore, the Mn content is preferably 7.00% or less. The Mn content is more preferably 5.00% or less, and further preferably 3.50% or less.

[0057] P: 0.100% or less

[0058] P is an element that reduces corrosion resistance and hot workability. If the P content exceeds 0.100%, the adverse effects on corrosion resistance and hot workability become significant. Therefore, the P content is preferably 0.100% or less. The P content is more preferably 0.070% or less, and further preferably 0.040% or less. It should be noted that the P content may be 0%. In addition, from the viewpoint of avoiding excessive P removal and resulting in increased costs, the P content is preferably 0.010% or more.

[0059] S: 0.030% or less

[0060] S is an element that reduces corrosion resistance and hot workability. If the S content exceeds 0.030%, the adverse effects on corrosion resistance and hot workability become significant. Therefore, the S content is preferably 0.030% or less. The S content is more preferably 0.010% or less, and further preferably 0.005% or less. It should be noted that the S content may be 0%. In addition, from the viewpoint of avoiding excessive desulfurization and resulting in increased costs, the S content is preferably 0.001% or more.

[0061] Al: 0.100% or less

[0062] Al is an element that acts as a deoxidizer. In order to obtain this effect, it is preferred to contain 0.001% or more of Al. However, if the Al content exceeds 0.100%, nitrides are formed and become the cause of surface defects. Therefore, the Al content is preferably 0.100% or less. The Al content is more preferably 0.050% or less, and further preferably 0.015% or less.

[0063] Cu: 4.00% or less

[0064] Cu is a γ phase generating element and has the effect of increasing the γ phase fraction. In order to obtain this effect, it is preferred to contain 0.01% or more of Cu. On the other hand, if the Cu content exceeds 4.00%, the high temperature strength increases, resulting in a decrease in hot workability. Therefore, the Cu content is preferably 4.00% or less. The Cu content is more preferably 2.00% or less, and further preferably 1.50% or less.

[0065] Mo: 4.00% or less

[0066] Mo has the effect of improving corrosion resistance. In order to obtain this effect, it is preferred to contain 0.01% or more of Mo. On the other hand, if the Mo content exceeds 4.00%, the high temperature strength increases, resulting in a decrease in hot workability. Therefore, the Mo content is preferably 4.00% or less. The Mo content is more preferably 2.00% or less, and further preferably 0.50% or less.

[0067] Ti: 0.50% or less

[0068] Ti has the effect of preventing sensitization and improving the corrosion resistance of steel. Therefore, depending on the required characteristics, for example, it is preferable to contain 0.01% or more of Ti. However, if the Ti content exceeds 0.50%, coarse Ti nitrides are formed, which become the main cause of surface roughness and coating defects during cold rolling. Therefore, the Ti content is preferably 0.50% or less. The Ti content is more preferably 0.20% or less.

[0069] Nb: 0.50% or less

[0070] Nb has the effect of preventing sensitization and improving the corrosion resistance of steel. Therefore, according to the required characteristics, for example, it is preferable to contain 0.01% or more of Nb. However, if the Nb content exceeds 0.50%, the hot workability decreases. Therefore, the Nb content is preferably 0.50% or less. The Nb content is more preferably 0.20% or less.

[0071] V: 0.50% or less

[0072] V is an element that refines the steel structure and improves the strength. Therefore, depending on the required characteristics, for example, it is preferable to contain 0.01% or more of V. However, if the V content exceeds 0.50%, the hot workability decreases. Therefore, the V content is preferably 0.50% or less. The V content is more preferably 0.20% or less, and further preferably 0.10% or less.

[0073] Zr: 0.50% or less

[0074] Zr is an element that refines the steel structure and improves the strength. Therefore, depending on the required characteristics, for example, it is preferable to contain 0.01% or more of Zr. However, if the Zr content exceeds 0.50%, the hot workability decreases. Therefore, the Zr content is preferably 0.50% or less. The Zr content is more preferably 0.20% or less, and further preferably 0.10% or less.

[0075] Sn: 0.50% or less

[0076] Sn is an element effective in suppressing surface roughness during rolling, and can be appropriately contained. In order to obtain this effect, it is preferred to contain 0.01% or more of Sn. On the other hand, if the Sn content exceeds 0.50%, hot workability decreases. Therefore, the Sn content is preferably 0.50% or less. The Sn content is more preferably 0.20% or less, and further preferably 0.10% or less.

[0077] B: 0.0100% or less, Ca: 0.0100% or less, and Mg: 0.0100% or less

[0078] B, Ca and Mg are all elements that improve hot workability and can be appropriately contained. In order to obtain this effect, it is preferred to contain 0.0003% or more of B, Ca and Mg respectively. On the other hand, if the contents of B, Ca and Mg each exceed 0.0100%, the corrosion resistance will be reduced. Therefore, when B, Ca and Mg are contained, each content is preferably 0.0100% or less. The contents of B, Ca and Mg are more preferably 0.0050% or less respectively.

[0079] REM: 0.10% or less

[0080] REM is an element that improves hot workability and can be appropriately contained. In order to obtain this effect, it is preferred to contain 0.01% or more of REM. On the other hand, if the REM content exceeds 0.10%, the corrosion resistance will be reduced. Therefore, the REM content is preferably 0.10% or less. The REM content is more preferably 0.05% or less. It should be noted that REM refers to Sc, Y and lanthanides (elements with atomic numbers 57 to 71 such as La, Ce, Pr, Nd, and Sm).

[0081] Components other than the above are Fe and inevitable impurities. It should be noted that, as an example of inevitable impurities, O (oxygen) can be mentioned. From the viewpoint of preventing surface defects caused by inclusions, it is preferable to control O (oxygen) to 0.05% or less.

[0082] [2]Steel structure

[0083] Next, the steel structure of the stainless steel plate according to one embodiment of the present invention will be described.

[0084] γ phase fraction: more than 30%

[0085] As described above, in order to achieve both excellent stamping workability and resistance to Fe ion dissolution, it is important to make an austenite-ferrite duplex stainless steel plate by appropriately controlling the Cr content, Ni content, and N content of the component composition as described above. Therefore, the γ phase fraction is made to be 30% or more. The γ phase fraction is preferably 40% or more. In addition, the γ phase fraction is preferably 80% or less, more preferably 70% or less, and further preferably 60% or less.

[0086] γ phase + α phase fraction: more than 95%

[0087] As described above, in order to take into account both excellent stamping workability and resistance to Fe ion dissolution, it is important to make an austenite-ferrite duplex stainless steel plate on the basis of appropriately controlling the Cr content, Ni content and N content of the component composition as described above. Therefore, the γ phase + α phase fraction is made to be 95% or more. The γ phase + α phase fraction is preferably 97% or more, more preferably 98% or more, and further preferably 99% or more. The upper limit of the γ phase + α phase fraction is not particularly limited and can be 100%.

[0088] It should be noted that the α phase fraction is preferably 20% or more, more preferably 30% or more, and further preferably 40% or more. In addition, the α phase fraction is preferably 70% or less, and more preferably 60% or less. In addition, the fraction of the remaining structure other than the γ phase and the α phase is preferably 5% or less. The fraction of the remaining structure is preferably 3% or less, more preferably 2% or less, and further preferably 1% or less. The lower limit of the fraction of the remaining structure is not particularly limited and may be 0%. As the remaining structure, for example, precipitates such as carbides can be cited.

[0089] Here, the γ phase fraction and the γ phase + α phase fraction are measured according to a conventional method, for example, as follows.

[0090] First, a test piece with a length of 15 mm and a width of 10 mm was taken from a stainless steel plate as a test material. Next, the test piece was embedded in resin so that the cross section parallel to the rolling direction became the observation surface, and the cross section was mirror-polished. Next, Murakami's reagent (10 g of potassium ferrocyanide, 10 g of potassium hydroxide, and 100 cm of pure water) was used to measure the surface of the test piece. 3 The test piece is stained with a coloring agent (aqueous solution mixed with water) and the test piece is observed using an optical microscope. By coloring with Murakami's reagent, only the α phase area is colored gray. That is, on the observation surface of the test piece, only the α phase area is etched to diffusely reflect light. Therefore, the α phase area is darker than the γ phase area and looks colored gray. On the other hand, the γ phase is not colored and remains in a white state. That is, on the observation surface of the test piece, the γ phase area is not etched, and the mirror polished surface is maintained, which looks bright. After distinguishing the γ phase area and the α phase area through the above observation, the area of ​​these areas is calculated by image analysis, and the ratio of the γ phase to the α phase is obtained. It should be noted that the observation using an optical microscope is performed on 5 viewing fields at a magnification of 200 times, and the average values ​​of the 5 viewing fields are respectively used as the γ phase fraction and the α phase fraction. In addition, the γ phase + α phase fraction is the sum of the γ phase fraction and the α phase fraction obtained in this way. In the above observation, the region where the residual structure such as precipitates appears black can be distinguished from the γ phase or the α phase and recognized.

[0091] [3] Mechanical properties, etc.

[0092] Next, mechanical properties and the like of a stainless steel plate according to an embodiment of the present invention will be described.

[0093] Total elongation (elongation at break): more than 40%

[0094] As described above, the separator is generally manufactured by punching a substrate plate to form a groove as a flow path for gas or cooling water. Therefore, the substrate plate as a blank material of the separator is required to have excellent punching workability. Specifically, the total elongation must be 40% or more. Therefore, the total elongation is set to be 40% or more.

[0095] Here, a tensile test was performed based on JIS Z 2241 to measure the total elongation.

[0096] It should be noted that “excellent punchability” means that the total elongation is 40% or more.

[0097] In addition, “excellent resistance to Fe ion dissolution” means that the amount of Fe ions eluted in the test solution is 70 μg / L or less in a polarization test under the following test conditions.

[0098] Test conditions

[0099] Test solution: Contains 0.1 ppm by mass of F - (Fluoride ion), pH: 3.0 sulfuric acid aqueous solution 400 mL

[0100] Test piece size (the size of the test piece in contact with the test liquid): 20 mm x 40 mm

[0101] Test potential: 0.6V vs SSE

[0102] Test time: 24 hours

[0103] More detailed test conditions are described in the examples described below.

[0104] Plate thickness: 0.03~0.30mm

[0105] From the perspective of the carrying space and weight of the fuel cell stack, the thickness of the stainless steel plate for the fuel cell separator according to one embodiment of the present invention is preferably 0.03 to 0.30 mm. If the thickness is less than 0.03 mm, the production efficiency of the stainless steel plate decreases. On the other hand, if the thickness exceeds 0.30 mm, the carrying space and weight of the fuel cell stack will increase. The thickness of the stainless steel plate for the fuel cell separator according to one embodiment of the present invention is more preferably 0.05 mm or more. In addition, the thickness of the stainless steel plate for the fuel cell separator according to one embodiment of the present invention is more preferably 0.15 mm or less.

[0106] [4]Coating with conductive materials

[0107] Furthermore, the stainless steel plate according to one embodiment of the present invention may have a coating layer of a conductive material on its surface.

[0108] Here, as the coating of the conductive substance, it is preferred to use a material having excellent corrosion resistance and conductivity in the use environment of the separator for fuel cells. The coating of the conductive substance is preferably, for example, a metal layer, an alloy layer, a metal oxide layer, a metal nitride layer, a metal carbide layer, a carbon material layer, a conductive polymer layer, an organic resin layer containing a conductive substance, or a mixture layer thereof.

[0109] Examples of the metal layer include Au, Ag, Cu, Pt, Pd, W, Sn, Ti, Al, Zr, Nb, Ta, Ru, Ir and Ni, among which Au and Pt metal layers are preferred.

[0110] In addition, as alloy layers, there can be cited Sn alloy layers such as Ni-Sn (Ni3Sn2, Ni3Sn4), Cu-Sn (Cu3Sn, Cu6Sn5), Fe-Sn (FeSn, FeSn2), Sn-Ag, Sn-Co, and alloy layers such as Ni-W, Ni-Cr, and Ti-Ta, among which alloy layers of Ni-Sn and Fe-Sn are preferred.

[0111] In addition, as metal oxide layers, there can be mentioned metal oxide layers such as SnO2, ZrO2, TiO2, WO3, SiO2, Al2O3, Nb2O5, IrO2, RuO2, PdO2, Ta2O5, Mo2O5 and Cr2O3, among which metal oxide layers of TiO2 and SnO2 are preferred.

[0112] In addition, as metal nitride layers and metal carbide layers, metal nitride layers and metal carbide layers such as TiN, CrN, TiCN, TiAlN, AlCrN, TiC, WC, SiC, B4C, molybdenum nitride, CrC, TaC and ZrN can be listed, among which the metal nitride layer of TiN is preferred.

[0113] Examples of the carbon material layer include graphite, amorphous carbon, diamond-like carbon, carbon black, fullerene, and carbon nanotube. Among them, graphite and diamond-like carbon are preferred.

[0114] In addition, examples of the conductive polymer layer include conductive polymer layers of polyaniline, polypyrrole, and the like.

[0115] In addition, the organic resin layer containing a conductive substance contains at least one conductive substance selected from the metal, alloy, metal oxide, metal nitride, metal carbide, carbon material and conductive polymer constituting the above-mentioned metal layer, alloy layer, metal oxide layer, metal nitride layer, metal carbide layer, carbon material layer and conductive polymer layer, and contains at least one organic resin selected from epoxy resin, phenolic resin, polyamide-imide resin, polyester resin, polyphenylene sulfide resin, polyamide resin, polyurethane resin, acrylic resin, polyethylene resin, polypropylene resin, carbodiimide resin, phenolic epoxy resin, etc. As such an organic resin layer containing a conductive substance, for example, a phenolic resin dispersed with graphite, an epoxy resin dispersed with carbon black, etc. are preferred.

[0116] It should be noted that the conductive material is preferably a metal or a carbon material (particularly graphite or carbon black). The content of the conductive material is not particularly limited as long as a predetermined conductivity in the separator of the fuel cell can be obtained.

[0117] In addition, as the above-mentioned mixture layer, for example, a mixture layer of Ni—Sn alloy in which TiN is dispersed can be cited.

[0118] [5] Suitable manufacturing method

[0119] Next, a preferred method for producing a stainless steel plate for a fuel cell separator according to one embodiment of the present invention will be described.

[0120] For example, the steel having the above-mentioned composition is melted in a converter or an electric furnace and refined by VOD (Vacuum Oxygen Decarburization), AOD (Argon Oxygen Decarburization), etc. Next, a slab is made by blooming rolling or continuous casting. Then, the slab is heated to 1200-1300°C and hot-rolled to make a hot-rolled steel plate. Then, the obtained hot-rolled steel plate is arbitrarily subjected to hot-rolled plate annealing at 900-1200°C. Hot-rolled plate annealing can be performed by continuous annealing or by intermittent annealing. The intermediate annealing, bright annealing, and cold-rolled plate annealing described later are also the same. In addition, descaling is arbitrarily performed by pickling or grinding. In pickling, for example, a mixture of sulfuric acid or nitric acid and hydrofluoric acid can be used. It should be noted that the scale can be arbitrarily removed by shot blasting before pickling. Next, the hot-rolled steel sheet (or hot-rolled annealed steel sheet) is arbitrarily cold-rolled to form a cold-rolled steel sheet. It should be noted that when the work hardening caused by cold rolling is obvious, intermediate annealing can be arbitrarily performed. Next, the obtained cold-rolled steel sheet is bright annealed at 900 to 1200°C in a non-oxidizing atmosphere as cold-rolled sheet annealing. In addition, the cold-rolled sheet annealing can be performed in an oxidizing atmosphere instead of bright annealing. In the latter case, it is preferred to remove the generated oxide scale by pickling or grinding. Acid immersion or electrolytic etching is further performed to roughen the surface or remove the surface oxide film, and the growth of the passive film is promoted and modified.

[0121] In addition, a conductive coating may be applied to the surface of the obtained steel plate to form a coating of a conductive substance. It should be noted that the coating of a conductive substance is as described in [4] above. In addition, the conductive coating may be applied, for example, by physical vapor deposition (PVD) such as sputtering, vacuum evaporation, ionized evaporation or ion plating. In addition, the conductive coating may be applied by electroplating, hot dip plating, etc. In addition, a plurality of conductive coatings may be combined. In addition, the conductive coating may be applied after the stainless steel plate is processed into a partition shape.

[0122] In this manner, the stainless steel plate according to one embodiment of the present invention can be manufactured.

[0123] Example

[0124] A 50 kg steel ingot having the composition shown in Table 1 (the remainder is Fe and unavoidable impurities) is produced. Next, the steel ingot is hot rolled to produce a hot rolled steel plate with a plate thickness of 3 mm. Next, the hot rolled steel plate is subjected to hot rolled plate annealing in the atmosphere at a temperature range of 900°C to 1200°C for 1 minute to obtain a hot rolled annealed steel plate. Next, the surface oxide scale of the hot rolled annealed steel plate is removed by grinding with a grinder. Next, the hot rolled annealed steel plate is cold rolled to a plate thickness of 0.1 mm, and cold rolled plate annealing is carried out in an atmosphere of nitrogen: 25 volume % + hydrogen: 75 volume % at 900°C to 1200°C for 1 minute to obtain a cold rolled annealed steel plate. For the cold rolled annealed steel plate thus obtained, the steel structure is observed according to the above-mentioned method, and the γ phase fraction and the γ phase + α phase fraction are measured. The results are shown in Table 2.

[0125] In addition, (1) punchability and (2) resistance to Fe ion elution were evaluated according to the following procedures. The results are shown in Table 2.

[0126] (1) Stamping processability

[0127] From the cold-rolled annealed steel sheet obtained as described above, a JIS 13B tensile test piece was taken in a manner that the long side direction of the tensile test piece was parallel to the rolling direction. Next, using the tensile test piece taken, a tensile test was performed based on JIS Z 2241 under the condition of a crosshead speed of 10 mm / min to measure the total elongation. Then, the stamping workability was evaluated according to the following criteria.

[0128] Qualified (excellent): total elongation is more than 40%

[0129] Unqualified (bad): total elongation less than 40%

[0130] (2) Resistance to Fe ion dissolution

[0131] The polarization test was conducted in an environment simulating the use environment of the separator of the fuel cell, and the Fe ion elution resistance was evaluated by analyzing the amount of Fe ions eluted in the test solution after the test.

[0132] Specifically, a test piece of 20 mm × 50 mm size was taken from the cold-rolled annealed steel sheet obtained as described above. Next, the surface and back of the test piece were ground with #800 grinding paper. Next, a lead made of SUS304 was installed at one end of the short side of the test piece by spot welding, and the lead was covered with a Teflon (registered trademark) tube. Next, as Figure 1As shown in FIG. 1 , the surface, back and end faces of the 20 mm × 10 mm area at the end of the test piece to which the lead wire is welded are covered with NITOFLON (registered trademark) tape. Then, the 20 mm × 40 mm area (surface, back and end faces) other than the area covered with NITOFLON (registered trademark) tape is used as the test area. The test piece thus obtained is immersed in a test solution containing 0.1 wt ppm of F - (Fluoride ion) pH: 3.0 in 400 mL of sulfuric acid aqueous solution, maintained at a potential of 0.6 V vs SSE for 24 hours. After holding, the test solution was taken and analyzed by inductively coupled plasma mass spectrometry (ICP-MS) to determine the amount of Fe ion dissolution. Then, the Fe ion dissolution resistance was evaluated according to the following criteria.

[0133] Pass (excellent): Fe ion elution is 70 μg / L or less

[0134] Unqualified (bad): The amount of Fe ions dissolved exceeds 70μg / L

[0135]

[0136]

[0137] According to Table 2, in all the examples of the present invention, both excellent punchability and resistance to Fe ion dissolution were achieved.

[0138] On the other hand, since the Ni content of Sample Nos. 6 to 8 as comparative examples exceeded the appropriate range, sufficient resistance to Fe ion dissolution could not be obtained.

[0139] In addition, since the Cr content of sample No. 9 exceeds the appropriate range, the γ phase fraction does not satisfy the appropriate range, and sufficient stamping workability cannot be obtained.

[0140] Since the N content of Sample No. 10 and Sample No. 11 does not satisfy the appropriate range, the γ phase fraction does not satisfy the appropriate range, and sufficient stamping workability cannot be obtained.

[0141] Industrial Applicability

[0142] According to the present invention, a stainless steel sheet having both excellent press workability and resistance to Fe ion elution can be obtained, and thus the present invention is extremely useful industrially.

Claims

1. An austenitic ferritic duplex stainless steel plate for a fuel cell separator, the composition of which is Cr: 18.0-24.0%, Ni: 3.00% or less, and N: 0.100-0.300%, in terms of mass %. The steel structure has austenite phase and ferrite phase. The fraction of the austenite phase is 30% or more, The total fraction of the austenite phase and the ferrite phase is 95% or more, The total elongation is more than 40%.

2. The austenitic-ferritic duplex stainless steel plate for a fuel cell separator according to claim 1, wherein: The plate thickness is 0.03~0.30mm.

3. The austenitic-ferritic duplex stainless steel sheet for a fuel cell separator according to claim 1 or 2, wherein: A coating of conductive material on the surface.